Fe-N-C cathode oxygen reduction catalyst based on Fe supramolecules and preparation method of Fe-N-C cathode oxygen reduction catalyst

By using the preparation method of Fe-N-C cathode oxygen reduction catalyst based on Fe supramolecular in fuel cells, the problem of dissolution of the active site and insufficient site density of the catalyst is solved, and a catalyst with high activity and stability is achieved, which is suitable for large-scale production.

CN119581582AActive Publication Date: 2025-03-07UNIV OF SCI & TECH OF CHINA
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411852292.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-07
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing Fe-N-C catalysts have a problem of degradation in the dissolution of active sites under fuel cell conditions, and it is difficult to improve single-atom site density and stability.

Method used

Using the preparation method of Fe-N-C cathode oxygen reduction catalyst based on Fe supramolecular, the first pyrolysis of ZIF-8 in a protective atmosphere is used to obtain a carbon-nitrogen substrate, and then ultrasonic dispersed with the iron supramolecular precursor in water, and a second pyrolysis is performed to form a Fe-N-C catalyst with a positive dodecahedral frame structure.

Benefits of technology

The single-atom site density and stability of the catalyst are improved, the catalytic activity of oxygen reduction is enhanced, and the method is simple and easy to perform, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581582A_ABST
    Figure CN119581582A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a Fe-N-C cathode oxygen reduction catalyst based on Fe supramolecules, and the preparation method comprises the following steps: in a protective atmosphere, carrying out first pyrolysis on ZIF-8 to obtain a carbon-nitrogen substrate which has a regular dodecahedron frame structure; under the stirring condition, the mixed solution is added into the melamine solution, an iron supramolecular precursor is obtained, and the mixed solution comprises cyanuric acid, iron ions and oxalate ions; and performing ultrasonic dispersion on the iron supramolecular precursor and a carbon-nitrogen substrate in water to obtain a catalyst precursor, and performing secondary pyrolysis on the catalyst precursor to obtain the Fe-N-C cathode oxygen reduction catalyst. The invention further provides the Fe-N-C cathode oxygen reduction catalyst obtained on the basis of the preparation method and application of the Fe-N-C cathode oxygen reduction catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure belongs to the technical field of catalysts and their preparation, and particularly relates to an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules and a preparation method thereof. Background Art

[0002] Fuel cells are a clean and efficient way to utilize energy, and are of great significance for environmental improvement and sustainable development. Developing highly active, stable, and economical cathode oxygen reduction reaction catalysts is of great practical significance for promoting the application of fuel cells.

[0003] Due to the high cost and low reserves of platinum, Fe-NC catalysts that do not contain platinum group metals are considered to be a promising oxygen reduction catalyst due to their low cost and high efficiency. In the process of synthesizing single Fe atoms, a high-temperature pyrolysis step is usually included to form Fe-N4 active sites with oxygen reduction catalytic activity. However, the pyrolysis step usually also leads to the agglomeration of Fe atoms, which limits the increase in the density of Fe single atom sites. At the same time, under fuel cell operating conditions, cathode Fe-NC catalysts usually also face the problem of active site dissolution leading to performance degradation. How to synthesize single-atom Fe-NC catalysts with high loading, high activity and high stability has attracted widespread attention.

[0004] In related technologies, single-atom iron catalysts can be prepared by strategies such as cage-encapsulated precursor pyrolysis to avoid the aggregation of Fe atoms. For example, a zeolitic imidazolate framework (ZIF-8) was used as a molecular cage to separate and encapsulate the metal precursor iron acetate (molecular diameter approximately 9.7 Å). After high-temperature pyrolysis, the resulting catalyst possessed monodisperse Fe-N4 active sites. The addition of H2 to an inert argon atmosphere modulated the local coordination structure and site density of FeN4, resulting in excellent activity and stability in fuel cells. Furthermore, a Fe-NC catalyst with a high Fe single-atom loading (approximately 2.0 wt%) and utilization efficiency (90%) was synthesized using chemical vapor deposition on the ZIF-8 material.

[0005] Although the catalysts prepared above have a certain single-atom site density and oxygen reduction catalytic activity, compared with precious metal catalysts, the active site density is still low and the stability is not satisfactory.

[0006] Therefore, under the premise of ensuring the oxygen reduction catalytic activity, finding a method to increase the single atom site density of Fe-NC catalysts and avoid the agglomeration of iron atoms has far-reaching practical significance. Summary of the Invention

[0007] In view of this, in order to solve at least one technical problem in related technologies and other aspects, the present disclosure proposes a method for preparing an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules, comprising:

[0008] In a protective atmosphere, ZIF-8 is subjected to a first pyrolysis to obtain a carbon-nitrogen substrate, wherein the carbon-nitrogen substrate has a regular dodecahedral framework structure;

[0009] adding a mixed solution to a melamine solution under stirring to obtain an iron supramolecular precursor, wherein the mixed solution includes cyanuric acid, iron ions and oxalate ions;

[0010] The iron supramolecular precursor and the carbon nitrogen substrate are ultrasonically dispersed in water to obtain a catalyst precursor, and the catalyst precursor is subjected to a second pyrolysis to obtain a Fe-NC cathode oxygen reduction catalyst.

[0011] According to an embodiment of the present disclosure, the preparation method of ZIF-8 includes:

[0012] The methanol solution of zinc nitrate and the methanol solution of dimethylimidazole were mixed evenly to obtain a suspension, and ZIF-8 was obtained after centrifugation;

[0013] Wherein, the molar ratio of zinc nitrate to dimethylimidazole is 6:13.

[0014] According to an embodiment of the present disclosure, in the first pyrolysis, the pyrolysis temperature is 900° C.-1100° C., and the heating rate is 3-10° C. / min.

[0015] According to an embodiment of the present disclosure, the preparation process of the mixed solution includes:

[0016] The oxalic acid solution and the iron salt are dispersed in water, and then the cyanuric acid solution is added and stirred evenly, wherein the molar ratio of oxalate ion to iron ion is 1:1-1:3.

[0017] According to an embodiment of the present disclosure, the mass ratio of the iron supramolecular precursor to the carbon nitride substrate is greater than 5.

[0018] According to an embodiment of the present disclosure, in the second pyrolysis, the temperature is first increased to 500°C-600°C at a heating rate of 3-10°C / min and maintained for 1-3 hours, and then increased to 900°C-1100°C at a heating rate of 3-10°C / min and maintained for 1-2 hours.

[0019] In another aspect of the present disclosure, an Fe-NC cathode oxygen reduction catalyst obtained by the aforementioned preparation method is also proposed, comprising: a carbon-nitrogen base having a regular dodecahedral framework structure and an active center; the active center is Fe-N4 loaded in the framework structure, and FeN4 exists in the form of a supramolecule.

[0020] According to an embodiment of the present disclosure, the mass fraction of active centers relative to the Fe-NC cathode oxygen reduction catalyst is 4 wt %-6 wt %.

[0021] In another aspect of the present disclosure, an application of the aforementioned Fe-NC cathode oxygen reduction catalyst in a fuel cell is also proposed.

[0022] According to an embodiment of the present disclosure, the fuel cell includes a hydrogen-oxygen fuel cell and a hydrogen-air fuel cell, and the peak power density of the hydrogen-oxygen fuel cell is 1.3-1.6 W / cm 2 The peak power density of hydrogen-air fuel cells is 0.6-0.8 W / cm 2 .

[0023] According to the embodiments of the present disclosure, cyanuric acid and melamine interact through non-covalent bonds to form ordered structural modules. These modules further guide and construct the basic framework of supramolecular iron. Oxalate ions can react with iron ions (such as Fe 3+ ) to form a stable coordination compound. The coordination effect not only contributes to the stable existence of iron ions but also provides an important structural basis for the formation of iron supramolecules. In the single-atom Fe-NC cathode oxygen reduction catalyst based on the Fe supramolecule form, the Fe atoms serve as active centers dispersed in the carbon-nitrogen matrix. The active center sites are well dispersed and highly concentrated, and have excellent oxygen reduction catalytic activity and stability. At the same time, the method provided by the present disclosure is simple and easy to implement, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope (SEM) image of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure;

[0025] Figure 2 This is a linear sweep voltammogram of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure in a 0.1 M perchloric acid solution;

[0026] Figure 3 This is a graph showing the change in three-electrode oxygen reduction performance of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure after an accelerated stability test (ADT) in a 0.1 M perchloric acid solution;

[0027] Figure 4 This is a polarization curve diagram of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure in hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cells;

[0028] Figure 5 This is the N 1s X-ray photoelectron spectrum of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure;

[0029] Figure 6 This is a comparison of the linear sweep voltammetry curves of the Fe-NC cathode oxygen reduction catalysts prepared in Examples 2 to 10 of the present disclosure in 0.1 M perchloric acid solution. DETAILED DESCRIPTION

[0030] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.

[0031] The endpoints of the ranges and any values ​​disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed in this disclosure.

[0032] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise," "include," etc. used herein indicate the presence of the features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.

[0033] All terms used herein (including technical and scientific terms) have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0034] It should be noted that, unless otherwise defined, technical or scientific terms used in this disclosure should have the ordinary meanings understood by persons of ordinary skill in the art to which this disclosure belongs. Where references to "first," "second," or the like are used throughout this disclosure, such references are intended solely to distinguish similar objects and should not be construed as indicating or implying their relative importance, order of precedence, or implicitly specifying the quantity of the technical features being referred to. References to "first," "second," or the like should be understood to be interchangeable where appropriate.

[0035] Similarly, in order to streamline the present disclosure and aid in understanding one or more of the various disclosed aspects, in the above description of exemplary embodiments of the present disclosure, the various features of the present disclosure are sometimes grouped together into a single embodiment, figure, or description thereof. Descriptions with reference to the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples" and the like mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present disclosure. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in an appropriate manner.

[0036] In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the fact that ordinary technicians in this field can implement them. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by this disclosure.

[0037] During the implementation of the present disclosure, it was found that in fuel cells, non-precious metal Fe-NC catalysts still require a higher catalyst loading to offset the lack of active site density. Traditional methods for preparing Fe-NC catalysts usually lead to the agglomeration of Fe atoms. Therefore, to develop stable single-atom Fe-NC catalysts with a high active site density, it is necessary to adopt appropriate strategies to inhibit the agglomeration of Fe atoms during pyrolysis, promote the dispersion of Fe atoms, and improve the stability of active sites, in order to obtain Fe-NC catalysts with excellent acidic oxygen reduction activity and stability.

[0038] The preparation method of the Fe-NC cathode oxygen reduction catalyst based on Fe supramolecule proposed in the present invention is to synthesize the Fe-NC cathode oxygen reduction catalyst based on Fe supramolecule by high-temperature pyrolysis of Fe supramolecule precursor and ZIF-8-NC precursor in a tube furnace under argon atmosphere protection. This method avoids the agglomeration of Fe atoms during the pyrolysis process to a certain extent, promotes the dispersion of Fe single atom sites, and greatly improves the catalytic activity of the catalyst under ORR conditions.

[0039] The present disclosure proposes a method for preparing a Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules, comprising the following steps S101 to S103:

[0040] Step S101: performing a first pyrolysis on ZIF-8 in a protective atmosphere to obtain a carbon-nitrogen substrate, wherein the carbon-nitrogen substrate has a regular dodecahedral framework structure.

[0041] In some specific embodiments, the obtained ZIF-8 is pyrolyzed at high temperature in a tube furnace under argon protection, and then cooled to room temperature naturally to obtain a carbon-nitrogen substrate (abbreviated as ZIF-8-NC).

[0042] Step S102: adding a mixed solution to the melamine solution under stirring to obtain an iron supramolecular precursor, wherein the mixed solution includes cyanuric acid, iron ions and oxalate ions.

[0043] In some specific embodiments, melamine and cyanuric acid were dispersed in water at 80°C, designated as solutions A and B, respectively. Separately, oxalic acid dihydrate and ferric nitrate nonahydrate were dispersed in water, designated as solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly added dropwise to solution A over 4 hours while stirring to produce an Fe supramolecular precursor.

[0044] Step S103: ultrasonically dispersing the iron supramolecular precursor and the carbon-nitrogen substrate in water to obtain a catalyst precursor, and performing a second pyrolysis on the catalyst precursor to obtain a Fe-NC cathode oxygen reduction catalyst.

[0045] In some specific examples, the resulting Fe supramolecular precursor is centrifuged, and the pyrolyzed ZIF-8-NC and water are added. The mixture is ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution is centrifuged again and dried in a 60°C vacuum oven overnight. The resulting composite solid is then pyrolyzed in a tube furnace to yield a Fe-NC cathode oxygen reduction catalyst based on the Fe supramolecular precursor.

[0046] According to the embodiments of the present disclosure, cyanuric acid and melamine interact through non-covalent bonds to form ordered structural modules. These modules further guide and construct the basic framework of supramolecular iron. Oxalate ions can react with iron ions (such as Fe 3+ ) to form a stable coordination compound. The coordination effect not only contributes to the stable existence of iron ions but also provides an important structural basis for the formation of iron supramolecules. In the single-atom Fe-NC cathode oxygen reduction catalyst based on the Fe supramolecule form, the Fe atoms serve as active centers dispersed in the carbon-nitrogen matrix. The active center sites are well dispersed and highly concentrated, and have excellent oxygen reduction catalytic activity and stability. At the same time, the method provided by the present disclosure is simple and easy to implement, and is suitable for large-scale production.

[0047] According to an embodiment of the present disclosure, the preparation method of ZIF-8 includes:

[0048] The methanol solution of zinc nitrate and the methanol solution of dimethylimidazole were mixed evenly to obtain a suspension, and ZIF-8 was obtained after centrifugation;

[0049] According to the embodiments of the present disclosure, the methanol solution of zinc nitrate and the methanol solution of dimethylimidazole ensure that the prepared ZIF-8 is a metal-organic framework material with a regular dodecahedral structure. This structure is conducive to the distribution of the active center FeN4 in the form of single atoms, thereby improving the catalytic mass transfer efficiency.

[0050] In some specific embodiments, 6 g of zinc nitrate hexahydrate is dissolved in 80 mL of methanol and 13 g of dimethylimidazole is dissolved in 160 mL of methanol at room temperature. The two are stirred and dissolved, mixed, and stirred for 24 h to obtain a suspension. The suspension is centrifuged, and the resulting solid is washed three times with methanol to obtain pure ZIF-8, which is then dried in a vacuum drying oven at 60°C overnight. Specifically, the separation method can be centrifugal separation, the speed can be 10,000 rpm, and the time can be 3 min; the washing method can be centrifugal washing, the speed can be 10,000 rpm, and the time can be 3 min, and a total of three washes are required.

[0051] According to an embodiment of the present disclosure, in the first pyrolysis, the pyrolysis temperature is 900℃-1100℃, for example, it can be selected as 900℃, 950℃, 1000℃, 1050℃, 1100℃, etc., and the heating rate is 3-10℃ / min, for example, it can be 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, etc.

[0052] According to an embodiment of the present disclosure, the preparation process of the mixed solution includes:

[0053] The oxalic acid solution and the iron salt are dispersed in water, and then the cyanuric acid solution is added and stirred evenly, wherein the molar ratio of oxalate ion to iron ion is 1:1-1:3, for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, etc.

[0054] According to an embodiment of the present disclosure, the mass ratio of the iron supramolecular precursor to the carbon nitride substrate is greater than 5.

[0055] According to an embodiment of the present disclosure, in the second pyrolysis, the temperature is first increased to 500°C-600°C at a heating rate of 3-10°C / min and maintained for 1-3 hours, wherein the heating rate can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc. The temperature of the first heating can be 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, etc., and the first holding time can be 1 hour, 2h, 3h, etc.; then heat the temperature to 900℃-1100℃ at a heating rate of 3-10℃ / min, and maintain for 1-2h, wherein the heating rate can be 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, etc., the second heating temperature can be 900℃, 950℃, 1000℃, 1050℃, 1100℃, etc., and the first insulation time can be 1h, 1.5h, 2h, etc.;.

[0056] In another aspect of the present disclosure, an Fe-NC cathode oxygen reduction catalyst obtained by the aforementioned preparation method is also proposed, comprising: a carbon-nitrogen base having a regular dodecahedral framework structure and an active center; the active center is Fe-N4 loaded in the framework structure, and FeN4 exists in the form of a supramolecule.

[0057] According to the embodiments of the present disclosure, compared with existing non-precious metal MNC catalysts, the present disclosure adds Fe supramolecules on the basis of ZIF-8-NC to promote the formation of Fe single-atom sites and avoid the agglomeration of Fe atoms, so that the activity and stability of the Fe-NC cathode oxygen reduction catalyst are better and the site density is higher.

[0058] According to an embodiment of the present disclosure, the mass fraction of active centers relative to the Fe-NC cathode oxygen reduction catalyst is 4 wt %-6 wt %.

[0059] According to the embodiments of the present disclosure, the density of Fe-N4 active sites in the catalyst is significantly increased thanks to the precise introduction and distribution control of Fe supramolecules. This not only means that more reactions can proceed simultaneously on the catalyst surface, but also accelerates the reaction rate, further improving catalytic efficiency.

[0060] In another aspect of the present disclosure, an application of the aforementioned Fe-NC cathode oxygen reduction catalyst in a fuel cell is also proposed.

[0061] According to the embodiments of the present disclosure, the Fe-NC cathode oxygen reduction catalyst exhibits higher catalytic activity under ORR conditions due to the high density distribution of Fe single-atom sites and the avoidance of agglomeration effects. Furthermore, the stable single-atom structure enhances the long-term stability of the catalyst, enabling it to maintain excellent performance during the continuous reaction process.

[0062] According to an embodiment of the present disclosure, the fuel cell includes a hydrogen-oxygen fuel cell and a hydrogen-air fuel cell, and the peak power density of the hydrogen-oxygen fuel cell is 1.3-1.6 W / cm 2 The peak power density of hydrogen-air fuel cells is 0.6-0.8 W / cm 2 It should be noted that the embodiments described are only part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, other embodiments obtained by ordinary technicians in this field without making creative work are all within the scope of protection of the present disclosure.

[0063] Example 1

[0064] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0065] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0066] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 226.9 mg of oxalic acid dihydrate and 241.8 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0067] The resulting Fe supramolecular precursor was centrifuged, and 120 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0068] The dried composite solid was heated to 550 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 2 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0069] Scanning electron microscopy imaging of the Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 1 was performed.

[0070] Figure 1 This is a scanning electron microscope (SEM) image of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure.

[0071] like Figure 1 As shown, the catalyst obtained in Example 1 has a relatively complete ZIF-8 morphology, no obvious metal particles appear, and iron self-assembles into a supramolecular form.

[0072] The Fe-NC cathode oxygen reduction catalyst based on the Fe supramolecule of Example 1 was subjected to linear sweep voltammetry in a 0.1 M perchloric acid solution. The linear sweep voltammetry test was conducted over a potential range of 1.03 V to 0.05 V (vs RHE), at a sweep rate of 20 mV / s, using a rotating disk electrode at 900 rpm.

[0073] Figure 2 This is a linear sweep voltammogram of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure in 0.1 M perchloric acid solution.

[0074] like Figure 2 As shown, the catalyst obtained in Example 1 exhibited excellent acidic oxygen reduction activity, with a half-wave potential of 0.87 V, which is close to that of commercial platinum-carbon catalysts. This demonstrates that the oxygen-etched Fe-NC cathode oxygen reduction catalyst obtained in Example 1 has high electrode activity in the electrochemical reaction and can more effectively promote the electrochemical reaction.

[0075] An accelerated stability test was performed on the Fe-NC cathode oxygen reduction catalyst based on the Fe supramolecule of Example 1 in a 0.1 M perchloric acid solution.

[0076] Figure 3 This is a graph showing the changes in the three-electrode oxygen reduction performance of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure after an accelerated stability test (ADT) in a 0.1 M perchloric acid solution.

[0077] like Figure 3As shown, after 30,000 cycles of accelerated stability testing at 0.6 V-0.95 V in a three-electrode system, the obtained catalyst showed excellent acidic oxygen reduction stability, with a half-wave potential decay of only 20 mV and excellent corrosion resistance.

[0078] Polarization curve tests were conducted on the membrane electrode using the Fe-NC cathode oxygen reduction catalyst based on the Fe supramolecule of Example 1 as a cathode catalyst in hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cells.

[0079] Figure 4 This is a polarization curve diagram of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure in hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cells.

[0080] like Figure 4 As shown, the obtained catalyst exhibits excellent fuel cell performance as a cathode oxygen reduction catalyst in the membrane electrode prepared.

[0081] Figure 5 This is the N 1s X-ray photoelectron spectrum of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure.

[0082] like Figure 5 As shown, the catalyst prepared in Example 1 has a higher pyrrole nitrogen content, which helps to improve the activity of single-atom sites.

[0083] Example 2

[0084] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0085] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0086] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 226.9 mg of oxalic acid dihydrate and 241.8 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0087] The resulting Fe supramolecular precursor was centrifuged, and 100 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0088] The dried composite solid was heated to 550 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 2 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0089] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 2 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0090] Example 3

[0091] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0092] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0093] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 226.9 mg of oxalic acid dihydrate and 241.8 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0094] The resulting Fe supramolecular precursor was centrifuged, and 150 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0095] The dried composite solid was heated to 550 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 2 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0096] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 3 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0097] Example 4

[0098] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0099] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0100] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 151.3 mg of oxalic acid dihydrate and 161.2 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0101] The resulting Fe supramolecular precursor was centrifuged, and 120 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0102] The dried composite solid was heated to 550 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 2 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0103] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 4 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0104] Example 5

[0105] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0106] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0107] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 151.3 mg of oxalic acid dihydrate and 161.2 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0108] The resulting Fe supramolecular precursor was centrifuged, and 100 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0109] The dried composite solid was heated to 550 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 2 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0110] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 5 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0111] Example 6

[0112] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0113] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0114] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 151.3 mg of oxalic acid dihydrate and 161.2 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0115] The resulting Fe supramolecular precursor was centrifuged, and 150 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0116] The dried composite solid was heated to 550 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 2 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0117] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 6 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0118] Example 7

[0119] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0120] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0121] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 226.9 mg of oxalic acid dihydrate and 241.8 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0122] The resulting Fe supramolecular precursor was centrifuged, and 120 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0123] The dried composite solid was heated to 600 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 2 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0124] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 7 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0125] Example 8

[0126] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0127] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0128] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 226.9 mg of oxalic acid dihydrate and 241.8 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0129] The resulting Fe supramolecular precursor was centrifuged, and 120 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0130] The dried composite solid was heated to 550 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 4 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0131] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 8 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0132] Example 9

[0133] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0134] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0135] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 226.9 mg of oxalic acid dihydrate and 241.8 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0136] The resulting Fe supramolecular precursor was centrifuged, and 120 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0137] The dried composite solid was heated to 600 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 4 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0138] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 9 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0139] Example 10

[0140] At room temperature, 6 g of zinc nitrate hexahydrate and 13 g of dimethylimidazole were dispersed in 80 mL and 160 mL of methanol, respectively. After stirring to dissolve, the mixture was mixed and stirred for 24 h. The suspension was centrifuged and the resulting solid was washed three times with methanol to obtain pure ZIF-8, which was then dried in a vacuum drying oven at 60°C overnight.

[0141] The obtained ZIF-8 was heated to 950 °C at a heating rate of 5 °C / min in a tube furnace under argon protection and maintained for 1 h, and then naturally cooled to room temperature to obtain carbon-nitrogen-based ZIF-8-NC.

[0142] 378 mg of melamine and 309 mg of cyanuric acid were dispersed in 80 mL and 64 mL of water at 80°C, respectively, labeled solutions A and B. Separately, 189.1 mg of oxalic acid dihydrate and 201.5 mg of ferric nitrate nonahydrate were dispersed in 56 mL of water, labeled solution C. Solution C and solution B were mixed and stirred for 10 minutes. The resulting mixture was then slowly dripped into the stirring solution A over 4 hours to obtain the Fe supramolecular precursor.

[0143] The resulting Fe supramolecular precursor was centrifuged, and 120 mg of pyrolyzed ZIF-8-NC and 50 mL of water were added. The mixture was ultrasonically dispersed for 5 minutes and stirred at room temperature for 12 hours. The solution was centrifuged again and dried in a vacuum oven at 60°C overnight.

[0144] The dried composite solid was heated to 550 °C in a tube furnace at a heating rate of 5 °C / min and maintained for 2 h. It was then heated to 950 °C at a heating rate of 5 °C / min and maintained for 1 h. It was then naturally cooled to room temperature to obtain an Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules.

[0145] The Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules of Example 11 was subjected to scanning electron microscopy, linear sweep voltammetry, accelerated stability, hydrogen-oxygen and hydrogen-air proton exchange membrane fuel cell analysis, and the results were similar to those of Example 1.

[0146] Figure 6 This is a comparison of the linear sweep voltammetry curves of the Fe-NC cathode oxygen reduction catalysts prepared in Examples 2 to 10 of the present disclosure in 0.1 M perchloric acid solution.

[0147] like Figure 6 As shown, the catalysts obtained in different examples have similar three-electrode half-wave potentials, which verifies that the Fe-NC cathode oxygen reduction catalyst based on Fe supramolecules proposed in the present disclosure has good stability.

[0148] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above are only specific embodiments of the present disclosure and are not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the scope of protection of the present disclosure.

Claims

1. A method for preparing a Fe-NC cathode oxygen reduction catalyst based on Fe supramolecular, comprising: In a protective atmosphere, ZIF-8 is subjected to a first pyrolysis to obtain a carbon-nitrogen substrate, wherein the carbon-nitrogen substrate has a regular dodecahedral framework structure; Under stirring conditions, adding a mixed solution to a melamine solution to obtain an iron supramolecular precursor, wherein the mixed solution includes cyanuric acid, iron ions and oxalate ions; The iron supramolecular precursor and the carbon-nitrogen substrate are ultrasonically dispersed in water to obtain a catalyst precursor, and the catalyst precursor is pyrolyzed for a second time to obtain a Fe-NC cathode oxygen reduction catalyst.

2. The preparation method according to claim 1, wherein The preparation method of ZIF-8 comprises: The methanol solution of zinc nitrate and the methanol solution of dimethylimidazole were mixed evenly to obtain a suspension, and ZIF-8 was obtained after centrifugation.

3. The preparation method according to claim 1, wherein In the first pyrolysis, the pyrolysis temperature is 900°C-1100°C, and the heating rate is 3-10°C / min.

4. The preparation method according to claim 1, wherein The preparation process of the mixed solution comprises: The oxalic acid solution and the iron salt are dispersed in water, and then the cyanuric acid solution is added and stirred evenly, wherein the molar ratio of the oxalate ion to the iron ion is 1:1-1:

3.

5. The preparation method according to claim 1, wherein The mass ratio of the iron supramolecular precursor to the carbonitride substrate is greater than 5.

6. The preparation method according to claim 1, wherein In the second pyrolysis, the temperature is first increased to 500-600°C at a heating rate of 3-10°C / min, maintained for 1-3 hours, and then increased to 900-1100°C at a heating rate of 3-10°C / min, maintained for 1-2 hours.

7. A Fe-NC cathode oxygen reduction catalyst obtained by the preparation method according to any one of claims 1 to 6, comprising: A carbon nitride substrate having a regular dodecahedral framework structure; The active center is Fe-N4 loaded in the framework structure, and the FeN4 exists in the form of a supramolecule.

8. The Fe-NC cathode oxygen reduction catalyst according to claim 7, wherein: The mass fraction of the active centers relative to the Fe-NC cathode oxygen reduction catalyst is 4 wt%-6 wt%.

9. Use of the Fe-NC cathode oxygen reduction catalyst according to any one of claims 1 or 8 in a fuel cell.

10. The use according to claim 9, wherein: The fuel cell includes a hydrogen-oxygen fuel cell and a hydrogen-air fuel cell. The peak power density of the hydrogen-oxygen fuel cell is 1.3-1.6 W / cm 2 The peak power density of the hydrogen-air fuel cell is 0.6-0.8 W / cm 2 .

Citation Information

Patent Citations

  • Two-dimensional carbon nitride supported iron monatomic catalyst as well as preparation method and application thereof

    CN114177927A

  • Preparation method of nitrogen-rich porous carbon material anchored metal ferroelectric catalyst

    CN114628693A

  • Preparation method and application of monatomic iron photoelectrode with carbon base as substrate

    CN114657593A

  • High-loading-capacity Fe monatomic nitrogen-doped porous carbon and preparation method and application thereof

    CN115799536A

  • Iron monatomic catalyst with controllable sulfur content and coordination mode and application thereof

    CN116637653A